Predicting Academic Achievement of the Students of Khuzestan Province Farhangian University Based on Kolb’s Learning Styles - Majid Hamdani (Universitas Ahmad Dahlan, 2021)
Considering that the courses of study are different in universities, students' academic achievement, which is often measured in terms of their academic grade point average, has close relationship with the students' various learning styles. In this research, the relationship between learning styles of the students of Farhangian University of Khuzestan Province and Kolb’s learning styles was investigated and their future successes were predicted. The sample related to this research consisted of 234 people who participated in the study randomly. The measurement tool was the standard questionnaire of Kolb’s learning styles with 12 questions in the form of 4 components and with appropriate reliability (0.88) by Cronbach's alpha coefficient method. Data analysis with Pearson correlation coefficient showed that there was a direct and significant relationship between students' learning style and students' academic achievement with grade point average criterion. On the other hand, using concurrent regression test, it was specified that both absorbing and divergent learning styles had the prediction capability of the academic achievement of the students of this university with the grade point average criterion.